Manuscritos de Vila Maria : edições fac-similar e semidiplomática - Sousa, José Maria de (2013)
The present dissertation, in light of philology, aims to prepare fac-similar and semidiplomatic editions of the manuscripts dated from 18th and 19th centuries, produced in Vila Maria, today Caceres town – MT, with the historic and paleographic aspects analysis, including onomastic index, according to the documents. The corpus is composed by one hundred of manuscripts, predominantly documents from portuguese colonial administratation, as letters and crafts, followed by patents and donation of land requests (sesmarias) to plantation or cattle ranch, military rank and orders, belonging to Mato Grosso Public Archive (APMT), Historic and Geographic Mato Grosso State Institute (IGHMT), Archive of Ultramarine Council/ Ultramarine Council (ACU/ CU). The historical and socio-economic-culturals contextualization of the period the colonial Brazil, Mato Grosso Capitancy and Vila Maria (/of Paraguay), Caceres town today, and aims to understand the factors were importants, colaborating to formation of the identity and values of population process of colonization as a village on the extreme west border of Brazil.